Benefits of progestin contraception in non‐allergic angioedema. Issue 4 (21st March 2013) - Saule, C.; Boccon‐Gibod, I.; Fain, O.; Kanny, G.; Plu‐Bureau, G.; Martin, L.; Launay, D.; Bouillet, L.; Gompel, A.
Summary Background Hereditary angioedema attacks can be induced or worsened by oral contraceptive containing oestrogens. Objectives The purpose of this study was to assess the impact of progestin contraceptives on angioedema attacks. Methods We conducted a French retrospective, multi‐centre study of progestin contraception in women with non‐allergic angioedema, including hereditary angioedema type I, II and III and idiopathic angioedema. Patients were classified into four groups according to frequency of attacks. We evaluated the effects of progestin on the mean number of attacks and compared the number of patients in each group before and under progestin contraception. The influence of hormonal factors on the course of angioedema was also assessed. Results Fifty‐five women were included: mean age was 32.1 years (16–52) and mean follow‐up 32.4 months (SD:29). Fourteen women were classified as type I (25.4%), two as type II (3.6%) and 19 as type III (34%) and 20 were idiopathic (36%). Seventeen patients were taking a low dose progestin‐only pill (POP), 24 antigonadotropic progestins (AGP) and 14 both successively. Total or partial improvement was observed in 81.8% (45/55) of the patients and more frequently in those on an AGP agent (34 patients, 89.5%) than on POP (19 patients, 61.3%) (P = 0.013). Conclusions & Clinical Relevance This is the first study evaluating the interest of antigonadotropic progestin contraception in a series of women with non‐allergic angioedema. Progestins, especially antigonadotropic progestins, appear to convey a marked benefit in most cases. Antigonadotropic progestins could thus be recommended as adjuvant treatment in childbearing women with non‐allergic angioedema.